Improvement of risk assessment in systemic light-chain amyloidosis using human placental growth factor - Kristen, Arnt; Rinn, Johannes; Hegenbart, Ute; Lindenmaier, David; Merkle, Corina; Röcken, Christoph; Hardt, Stefan; Giannitsis, Evangelos; Katus, Hugo (Clinical research in cardiology, 2015)
Vascular amyloid deposition is common in light-chain amyloidosis resulting in endothelial dysfunction. Human placental growth factor (PlGF), a member of the vascular endothelial growth factor family was found to be altered in diverse pathological conditions, e.g. endothelial dysfunction. This study evaluated the clinical role of PlGF in light-chain amyloidosis.